(untitled) (Cuadernos de Extensión Universitaria de la UNLPam, 2022)
The popular economy is made up of a diversity of actors, who are in collective projects of tangible solutions to the basic needs of working and obtaining family sustenance. In the province of La Pampa, social organizations and a municipality coordinate effort to develop a horticultural project that seeks to generate genuine work and responsibly produce healthy food. The objective of this work is to critically analyse the process and results of the first steps of self-diagnosis and the proposal of alternative solutions in the short and medium term. Within the framework of a university extension project, workshops were held under the guidelines of participatory action research. Based on the diagnosis of the current situation, the proposal of an improvement situation and the construction of alternative solutions, the project’s sustainability challenges are evident. Intangible aspects and the generation of internal and external synergies will be central to meeting the objectives and sustainability of the project.